TYPES OF CIVIL RELATIONS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The subject of this paper's research are the types of civil-legal relations, i.e., real-legal, obligation- legal, and inheritance-legal relations. The research in this paper has two primary objectives. The first objective is to show the similarities between the three types of civil-legal relations that connect these relations in the legal family called civil law. The second goal is to show the specifics of each of the three types of civil-legal relations by which they differ from each other.Through an analysis of the similarities between real-legal, obligation-legal and inheritance-legal relations, the points of connection between these branches of civil law will be shown, which are reflected in the common subject and method of regulating civil-legal relations. The paper will analyse more closely what is the subject of regulating civil-legal relations, as well as what are the specific methods of regulating civil-legal relations.The analysis of the specifics of real-legal, obligation-legal, and inheritance-legal relations will include a detailed presentation of the different nature, object and content of each of the three types of civil- legal relations. By presenting the specifics in the nature, object, and content of the three types of civil-legal relations, the paper will show their relative independence.
Keywords: civil law, real law, obligation law, inheritance law, legal relations.